2020
DOI: 10.1055/s-0040-1719212
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Behavior, and Stress Related to COVID-19 among Undergraduate Health Care Students in Jordan

Abstract: Objectives This study aimed to assess knowledge, attitude, and infection control measures related to the coronavirus disease 2019 (COVID-19) pandemic outbreak among Jordanian health care students. Besides, their social behavior and stress level regarding COVID-19 infection were assessed. Materials and Methods An online questionnaire was distributed to medical, dental, pharmacy, nursing, and applied health science students in Jordan during the COVID-19 outbreak quarantine in March 2020. The questionnaire compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 24 publications
3
30
1
5
Order By: Relevance
“…This risk has been further exacerbated by the lack of personal protective equipment (PPE) (5). The ever-increasing number of confirmed and suspected cases with coronavirus disease (COVID- 19), overwhelming workload, depletion of PPE, and lack of specific drugs has also had a significant negative impact on the mental health and well-being of HCWs with anxiety, depression, and psychological crisis being reported among the global healthcare workforce (6). To combat the disease, the WHO has emphasized the importance of accurate clear COVID-19-related health information as a means of dispelling misconceptions, mitigating fear, preventing discrimination, and ultimately eliminating future outbreaks of COVID-19 (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This risk has been further exacerbated by the lack of personal protective equipment (PPE) (5). The ever-increasing number of confirmed and suspected cases with coronavirus disease (COVID- 19), overwhelming workload, depletion of PPE, and lack of specific drugs has also had a significant negative impact on the mental health and well-being of HCWs with anxiety, depression, and psychological crisis being reported among the global healthcare workforce (6). To combat the disease, the WHO has emphasized the importance of accurate clear COVID-19-related health information as a means of dispelling misconceptions, mitigating fear, preventing discrimination, and ultimately eliminating future outbreaks of COVID-19 (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, for students to effectively practice in these roles, they need to be aware of all government advisories, guidelines, and standardized prevention and protective measure for their safety and well-being. Despite efforts, investigations indicate that there are still students in pharmacy, dental, medical, and public health areas neglecting the benefit of social distancing, staying at home, and the use of other preventive measures, such as using sanitizer and masks due to attitudinal and behavioral issues (19)(20)(21)(22). Lessons learned from Ebola and severe acute respiratory syndrome (SARS) indicated that public perceptions, attitudes, and behaviors play an important role in the effective control of epidemic disease (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on knowledge and attitudes of dental students and dental school staff towards COVID-19 and necessary preparation against its transmission have shown promising results [ 40 , 41 , 71 , 96 , 97 ]. Of course, with the changes in the guidelines and rules for infection control after the pandemic and new content that is discovered and published daily on the COVID-19 virus, it is necessary for students, faculty members, and staff to be trained and updated about the virus itself and how to deal with it [ 145 – 148 ]. Passing the training course in connection with covid-19 would have a direct relationship with improve in participants’ knowledge [ 41 , 149 – 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increasing efforts of handwashing and general hygiene as an essential step in COVID-19 prevention might trigger the obsession with contamination and compulsive hand washing, which are reported as common symptoms of OCD ( 25 , 50 ). Previous reports on the undergraduate medical students at Jordanian universities indicated high levels of adopting anti-COVID-19 precautionary measures, including social isolation strategies, avoiding crowded places, canceling traveling plans, canceling social events, changing life habits, regular hand washing, and enhanced personal hygiene measures ( 51 , 52 ). However, these studies did not measure the potential psychological effects of these preventive measures among such a vulnerable group of the population.…”
Section: Introductionmentioning
confidence: 99%